Case Report: Complete Response of Primary Massive Hepatocellular Carcinoma to Anti-Programmed Death Ligand-1 Antibody Following Progression on Anti-Programmed Death-1 Antibody - Liu, Gang; Zhou, Wenxuan; Li, Xiaoli; Guo, Lijie; He, Tingting; Zhao, Juan; Gong, Liansheng (Frontiers in Immunology, 2021)
Hepatocellular carcinoma (HCC) is an aggressive liver tumor that occurs from chronic liver disease, with high mortality rate limited treatment. Immune checkpoint inhibitors were successfully introduced to cancer therapy, among which inhibitors of programmed death ligand-1 (PD-L1) and receptor (PD-1) are more commonly selected for the treatment of HCC patients through along with through the combination of immunotherapy, including combined anti-vascular and dual immunotherapy. In this case study, we report a primary massive HCC patient with portal hepatic vein tumor thrombus who had a well response to atezolizumab in combination with bevacizumab, following progression of disease on combined immunotherapy of pembrolizumab and lenvatinib. This case demonstrates for the first time that HCC patient who is resistant to anti-PD-1 antibody immunotherapy can benefit from anti-PD-L1 antibody immunotherapy, providing a potentially promising strategy for the treatment of HCC.